2016
DOI: 10.1007/s12576-016-0485-9
|View full text |Cite
|
Sign up to set email alerts
|

The vital prognosis of elderly adults living in a group home in their mid-eighties

Abstract: The purpose of the present study is to evaluate the vital prognoses of elderly people in their mid-eighties living in a group home (GH) compared to age- and sex-matched outpatient clinic (OPC) in an observational study conducted over 6 years. We investigated the association between mortality and general, cardiac, and nutritional parameters, including eicosapentaenoic acid (EPA) in 54 GH residents (83 ± 8 years old) and 57 OPC attendees (83 ± 5 years old). Kaplan-Meier curves and Cox proportional hazard ratio a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…In the present study, we observed that low levels of Hb or Alb were associated with a poor prognosis in patients in home healthcare, which is in line with previous studies [ 3 , 9 , 18 ]. Low Alb levels are associated with malnutrition [ 18 ], undernutrition [ 23 ], and inflammation in non-cancerous diseases [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, we observed that low levels of Hb or Alb were associated with a poor prognosis in patients in home healthcare, which is in line with previous studies [ 3 , 9 , 18 ]. Low Alb levels are associated with malnutrition [ 18 ], undernutrition [ 23 ], and inflammation in non-cancerous diseases [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is the first description to indicate that AST, in addition to Hb and Alb, is an independent prognostic biomarker for older patients without cancer, who had a normal-to-mild increased level of AST, in the home healthcare settings. These findings suggest that the AST level could be measured at baseline and utilized in combination with the helpful biomarkers (Alb and Hb) as reported previously [ 3 , 9 - 10 ] for estimating prognosis in older patients. The time-dependent AUC of AST > 31 also increased by 360 days (Table 3 ).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Finally, 56 articles were selected to answer our research question. These articles described a total of seven distinctive innovative living arrangements: (1) small-scale living [ 15 , 16 , 18 , 29 39 ], (2) the green house model [ 40 47 ], (3) shared housing arrangements [ 48 – 54 ], (4) green care farms [ 20 , 55 61 ], (5) dementia villages [ 40 , 62 66 ], (6) group homes [ 67 69 ], and (7) intergenerational living [ 70 – 72 ]. Some articles, however, could not be grouped into one overarching living arrangement because they did not describe the same overarching elements (a household model of residential aged care [ 73 ], household model units [ 74 , 75 ], intensive service housing [ 76 ], a non-traditional residential care facility [ 77 ], the Woodside place model [ 78 ], a small-scale homelike unit [ 79 ], and a homelike dementia care facility [ 80 ]) and were described as an ‘other’ category.…”
Section: Resultsmentioning
confidence: 99%